NARRATING THE MUSEUM TO PROMOTE EMPATHY AND CRITICAL THINKING IN MEDICAL SCIENCE STUDENTS AND DOCTORS THROUGH ONLINE ACTIVITIES: A PILOT RESEARCH EXPERIENCE - Antonella Poce; Massimo Mancone; Maria Rosaria Re; Mara Valente; Carlo De Medio; Francesca Amenduni; Viviana Maestrini (Italian Journal of Educational Technology, 2021)
The research experience "Narrating the museum to promote empathy and critical thinking in medical science students and doctors through online activities", carried out within the "Inclusive Memory" project, co-funded by University Roma Tre, aims at promoting empathy and critical thinking skills in medical science students and doctors through heritage education activities. The innovative features of the research experience lie in the use of online activities, combining different learning methodologies: Visual Thinking Strategies, Reflective Questioning, Storytelling, and Object-Based Learning. The paper presents the results of the pilot activity carried out by the Centre for Museum Studies research group, based at the Department of Education – Roma Tre, in collaboration with the Sapienza University of Rome. It also describes the teaching activities, learning and evaluation tools used during the pilot experience, which involved 35 participants. The trial results highlight a statistically significant improvement in the Critical Thinking use of language indicators and an improvement of Sensitivity to the context empathy dimension; participants state that their levels of communication and critical thinking skills improved at the end of the activities and that the exercises foreseen stimulated reflection, observation, and interpretation.